Green catalysts AuNPs/CQDs from turmeric starch: an effective solution in 4-Nitrophenol reduction - Thi Hoa Le; Ta Thi Ngoc Anh; Nguyen Thi Thu Huong; Le Thi Thanh Nhi; Quoc Hien Nguyen; Thai Hoa Tran (Materials Research Express)
This paper presents a green synthesis method for growing carbon quantum dots (CQDs) from turmeric starch. The CQDs were then used as reducing agents and stabilizers to synthesize dual-shaped gold nanoparticles (AuNPs) with spherical and triangular shapes. In addition to the advantages of CQDs in catalysis, such as their large surface area and the presence of functional groups, including hydroxyl (-OH) and carbonyl (-C=O), as evidenced by FTIR analysis, the material also demonstrates excellent electron transfer efficiency. This efficiency is attributed to the synergistic interaction between AuNPs and the functional groups on CQDs, facilitating catalytic electron transfer processes in reducing 4-nitrophenol (4-NP). Furthermore, the obtained AuNPs/CQDs material benefits from the plasmonic properties of AuNPs, enhancing light absorption and accelerating catalytic reactions. As a result, AuNPs/CQDs have been successfully applied to effectively catalyze the reduction of 4-NP in aqueous media with high efficiency. The synergy between the plasmonic effect of AuNPs and the catalytic properties of CQDs results in a high catalytic efficiency and a fast reaction time of 20 min, making this method simple, rapid, scalable, and highly effective for environmental pollution remediation.